Which patients should be transported to the emergency department? A perpetual prehospital dilemma - Tohira, Hideo; Fatovich, D.; Williams, Teresa; Bremner, A.; Arendts, G.; Rogers, I.; Celenza, A.; Mountain, D.; Cameron, P.; Sprivulis, P.; Ahern, T.; Finn, Judith (2016)
Objective: To examine the ability of paramedics to identify patients who could be managed in the community and to identify predictors that could be used to accurately identify patients who should be transported to EDs. Methods: Lower acuity patients who were assessed by paramedics in the Perth metropolitan area in 2013 were studied. Paramedics prospectively indicated on the patient care record if they considered that the patient could be treated in the community. The paramedic decisions were compared with actual disposition from the ED (discharge and admission), and the occurrence of subsequent events (ambulance request, ED visit, admission and death) for discharged patients at the scene was investigated. Decision tree analysis was used to identify predictors that were associated with hospital admission. Results: In total, 57183 patients were transported to the ED, and 10204 patients were discharged at the scene by paramedics. Paramedics identified 2717 patients who could potentially be treated in the community among those who were transported to the ED. Of these, 1455 patients (53.6%) were admitted to hospital. For patients discharged at the scene, those who were indicated as suitable for community care were more likely to experience subsequent events than those who were not. The decision tree found that two predictors (age and aetiology) were associated with hospital admission. Overall discriminative power of the decision tree was poor; the area under the receiver operating characteristic curve was 0.686. Conclusion: Lower acuity patients who could be treated in the community were not accurately identified by paramedics. This process requires further evaluation. © 2016 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine.